The development of coordination abilities of school-age children with visual disabilities - Магомедова [Liliana Magomedova], Ліліана Олеговна; Шестерова [Liudmila Shesterova], Людмила Єгорівна (Slobozhanskyi Herald of Science and Sport, 2013)
On the basis of the analysis of literary sources of the article gives characteristics of the coordination abilities, and shall specify sensitive periods of their development. Examines the role of sensory systems in the organization of activity of children with visual impairments and methodological approaches, which are used to increase the level of coordination abilities. Research data indicate a significant influence of the functional status of the sensor systems on the level of development of individual types of coordination abilities in children of school age, including those with visual disabilities. However, experts in the field of physical education and sport practically do not give recommendations for overcoming or correcting the existing shortcomings in the development of these important for children with impaired abilities. Analysis of the literature indicates a lack of attention of specialists to the development of the coordination abilities of children with visual disabilities through changes of functional state of analyzers systems, which, in our opinion, is a topical problem.